Sonic Hedgehog Activates the GTPases Rac1 and RhoA in a Gli-Independent Manner Through Coupling of Smoothened to Gi Proteins - Polizio, Ariel Héctor (2011)
The vertebrate Hedgehog (Hh) pathway has essential functions during development and tissue homeostasis in normal physiology, and its dysregulation is a common theme in cancer. The Hh ligands (Sonic Hh, Indian Hh, and Desert Hh) bind to the receptors Patched1 and Patched2, resulting in inhibition of their repressive effect on Smoothened (Smo). Smo is a seven-transmembrane protein, which was only recently shown to function as a G protein–coupled receptor (GPCR) with specificity toward the heterotrimeric guanine nucleotide-binding protein Gi. In addition to activating Gi, Smo signals through its C-terminal tail to inhibit Suppressor of Fused, resulting in stabilization and activation of the Gli family of transcription factors, which execute a transcriptional response to so-called “canonical Hh signaling.” In this Presentation, we illustrate two outcomes of Hh signaling that are independent of Gli transcriptional activity and, thus, are defined as “noncanonical.” One outcome is dependent on Smo coupling to Gi proteins and exerts changes to the actin cytoskeleton through stimulation of the small guanosine triphosphatases (GTPases) RhoA and Rac1. These cytoskeletal changes promote migration in fibroblasts and tubulogenesis in endothelial cells. Signaling through the other noncanonical Hh pathway is independent of Smo and inhibits Patched1-induced cell death.